Project Stages Interface among Construction Professionals in Lagos State, Nigeria - Taiwo, Richard Oluseyi; Morakinyo, Kolawole Opeyemi; Yusuff, Iskil O.; Oyeniyi, Samuel Ayobami (Local Engineering, 2025)
The study examined the interface problems in construction project stages among professionals in Lagos State, Nigeria. Primary information was obtained through structured questionnaire. The target population were construction professionals who had experienced interface problems at both the design and construction stages of projects in Lagos State. A total of two hundred and sixty (260) copies of completed questionnaire were retrieved through online and physical administration using snowball sampling technique for selection of respondents. Data were analyzed using exploratory factor analysis, confirmatory factor analysis and structural equation modelling. Findings revealed that the interface problems at the design stage are; inadequate specification of project data, problem of spotting component clashes at the beginning of design phase, difficulty in obtaining complete project documents leading to late issuance of some designs, design complexity, badly written contract documents, and too many adjustments whenever there is changes in designs while inadequate specialized quality-control team, serious doubting and ambiguity of interface conflicts, lack of system informing about new project data, bad value of construction, complicated construction process, incapability to forecast and bring resolution to challenges connected to new construction technological methods, financial and technical status of the constructor, poor communication among project team members and change based on instruction or command are the interface problems at the construction stage.